Working online, living offline: labour in the Internet Age. (1st July 2013) - Ursula Huws
Abstract : This paper begins by tracing changes in employment patterns since the middle of the 20th Century, arguing that the mid 2000s marked the beginning of a fourth distinctive phase, the earlier ones having begun, respectively, after the end of World War II, after the 1973 oil crisis, and after the end of the Cold War, around 1990. In this new phase, dubbed here the 'Internet Age', various tendencies with their origins in earlier periods have reached critical mass. These include a developed international division of labour, in both manufacturing and services and an employment landscape dominated by large transnational corporations able to draw on this global labour pool, using ICTs to manage their increasingly elaborate value chains. Many of these corporations have grown on the basis of the commodification of activities which previously lay outside the scope of profit making, including public services. The paper then discusses how and why online workers are at the front line of many of these developments, before going on to introduce the contents of this volume.